2016
DOI: 10.1002/14651858.cd006244.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Care delivery and self management strategies for adults with epilepsy

Abstract: BackgroundResearchers have criticised epilepsy care for adults for its lack of impact, stimulating the development of various service models and strategies to respond to perceived inadequacies. ObjectivesTo assess the effects of any specialised or dedicated intervention beyond that of usual care in adults with epilepsy. Search methodsFor the latest update of this review, we searched the Cochrane Epilepsy Group Specialized Register (9 December 2013), the Cochrane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 38 publications
2
61
0
1
Order By: Relevance
“…A growing body of literature, primarily in adult epilepsy, has shown promise for the effectiveness of self-management interventions. [5][6][7][8][9][10][11] However, a recent systematic review of 24 pediatric epilepsy self-management intervention studies revealed that none of the pediatric epilepsy interventions met criteria for Level I or II evidence. 12,13 Furthermore, in many cases, self-management outcomes were not well described, and there was a wide diversity of intervention targets and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature, primarily in adult epilepsy, has shown promise for the effectiveness of self-management interventions. [5][6][7][8][9][10][11] However, a recent systematic review of 24 pediatric epilepsy self-management intervention studies revealed that none of the pediatric epilepsy interventions met criteria for Level I or II evidence. 12,13 Furthermore, in many cases, self-management outcomes were not well described, and there was a wide diversity of intervention targets and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the centrality of education and advocacy in enabling PWE to self-manage their condition [47,48], as with other chronic diseases, safe and effective decision-making in relation to referral, diagnosis, treatment and management rely on having competent practitioners in primary, secondary and tertiary care [49]. In addition to leading on educational developments for PWE, findings indicate that the ESNs were also leading on educational capacity building initiatives D4 Reviewer of all SOPs developed as part of the strategic reform of epilepsy services in Ireland via the National Epilepsy Programme.…”
Section: Discussionmentioning
confidence: 99%
“…That guideline will be used nationally, so she had a big input into that. [40][41][42][43][44][45][46][47] involving the wider healthcare workforce, both within and outside their own organisation. This finding is important given the many unmet needs that PWE experience in relation to education and service provision [5][6][7][8]13,50,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other disease groups, systematic implementation of self-management support for people with epilepsy is extremely limited. But, epilepsy self-management programs, tested in randomized control trials with robust study samples, offer substantial promise to improve outcomes and their use could serve as a starting point to augment epilepsy self-management support [29–31]. …”
Section: Why Would Clinicians Want Patients To Manage Themselves?mentioning
confidence: 99%